Sikh diaspora : theory, agency, and experience - Hawley, Michael. (Numen Book Series, 2013)
Sikh Diaspora: Theory, Agency, and Experience is a collection of essays offering new insights into the diverse experiences of Sikhs beyond the Punjab. Moving beyond migration history and global in their scope, the essays in this volume draw from a range of methodological approaches to engage with diaspora theory, agency, space, social relations, and aesthetics. Rich in substantive content, these essays offer critical reflections on the concept of diaspora, and insight into key features of Sikh experience including memory, citizenship, political engagement, architecture, multiculturalism, gender, literature, oral history, kirtan, economics, and marriage.